2020
DOI: 10.47102/annals-acadmed.sg.202023
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Amitriptyline and Movement Disorders: Clinical Profile and Outcome

Abstract: Introduction: Amitriptyline (AMT) is a tricyclic antidepressant. In this review, we evaluate the clinical and epidemiological profile, pathological mechanisms and management of AMT-associated movement disorders. Materials and Methods: A search for relevant reports in 6 databases was performed. Studies that reported patients developed only ataxia or tremor after AMT use were excluded. Results: A total of 48 reports on 200 cases were found. AMT-associated movement disorders included myoclonus (n = 26), dyskinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Chau et al reported a patient with Creutzfeldt–Jakob disease-like syndrome induced by gabapentin toxicity, in which electrodiagnostic studies showed periodic sharp wave complexes [ 40 ]. A similar clinical manifestation with electrodiagnostic studies was already observed with amitriptyline [ 121 ] and fluoroquinolones [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…Chau et al reported a patient with Creutzfeldt–Jakob disease-like syndrome induced by gabapentin toxicity, in which electrodiagnostic studies showed periodic sharp wave complexes [ 40 ]. A similar clinical manifestation with electrodiagnostic studies was already observed with amitriptyline [ 121 ] and fluoroquinolones [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…The time from PHT start to DTN onset was the lowest among PHT-associated MDs. This is a characteristic feature of drug-induced DTN and was reported with antiepileptic drugs and tricyclic antidepressants[ 66 ]. An interesting fact is that DTN only occurred with the highest doses of PHT, which is a distinctive finding compared to the published literature.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, as expected, different antidepressant groups, which increase serotonergic neurotransmission, could also induce RLS. Regarding this hypothesis, besides SSRI/SNRIs, atypical antidepressant mirtazapine, tricyclic antidepressants, and other antidepressant groups could provoke RLS to different degrees (Rissardo and Caprara, 2020a, 2020b). But we did not find any statistically significant differences between SSRIs and SNRIs in terms of RLS (Table 4).…”
Section: Discussionmentioning
confidence: 99%